Students’ Vocabulary Mastery in Listening - Aminah Maulidah (UICELL, 2017)
Listening is ability to identify and understand what others are saying. This involves understanding a speaker’s accent or pronunciation, his grammar and his vocabulary, and grasping his meaning. Linguistic knowledge in this case vocabulary mastery is a problem faced by foreign language learners in listening. When the learner does not have good vocabulary mastery then the learner will be difficult to catch the message being heard. Vocabulary mastery here relate with word formation such as prefixes, suffixes, and Greek suffixes. The objective of this research is to find out the relationship of vocabulary mastery in terms of word formation in listening skill. The researcher uses a quantitative research by using survey method. The technique of data analysis is the statistical technique of correlation and regression. The population in this research is English Department students of Teacher Training and Education Faculty of Halu Oleo University who programmed Listening I course. The samples used are 39 students who selected randomly. Instrument used by the researcher is objective test (multiple choices).